PARTISIPASI AYAH DENGAN PRAKTIK IBU DALAM PEMBERIAN MAKAN BALITA - Suryati Suryati; Uwla Nurlailla (Coping: Community of Publishing in Nursing, 2021)
Adequate nutrition in children is determined by appropriate feeding patterns by parents. Based on previous studies, although the father said that his figure greatly influences the fulfillment of toddler nutrition, but because it has become a tradition that the father is in charge of fulfilling a living and the mother takes care of everything at home including taking care of the children, so that fathers have less opportunity to meet nutritional needs until they are actually consumed by children. Objective to determine the relationship between father's participation and mother's practice in feeding toddlers at Posyandu Melati, Bundelan Village. Research method This study is a quantitative study using a cross-sectional design, with a sample of 51 people in September 2021. The sampling technique used is non-probability sampling. The instruments used were the CFQ questionnaire for maternal practice in feeding and the ECLS-B questionnaire for father's participation. These results are based on the spearment test with value = 0.000 (? value <0.05), there is good father participation with a percentage of 74,50 and appropriate mother practice with a percentage of 76,47%. Conclusion there is a relationship between father's participation and mother's practice in feeding toddlers at Posyandu Melati, Bundelan Village.